Climate, landscape, habitat, and woodland management associations with hazel dormouse Muscardinus avellanarius population status. (3rd June 2018) - Goodwin, Cecily E. D.; Suggitt, Andrew J.; Bennie, Jonathan; Silk, Matthew J.; Duffy, James P.; Al‐Fulaij, Nida; Bailey, Sallie; Hodgson, David J.; McDonald, Robbie A.
Abstract: Although strictly protected, populations of the hazel dormouse Muscardinus avellanarius in the UK declined by 72% from 1993 to 2014. Using National Dormouse Monitoring Programme data from 300 sites throughout England and Wales, we investigated variation in hazel dormouse population status (expressed as Indices of Abundance, Breeding, and population Trend) in relation to climate, landscape, habitat, and woodland management. Dormice were more abundant and produced more litters on sites with warmer, sunnier springs, summers, and autumns. Dormouse abundance was also higher on sites with consistently cold local climate in winter. Habitat connectivity, woodland species composition, and active site management were all correlated with greater dormouse abundance and breeding. Abundances were also higher on sites with successional habitats, whereas the abundance of early successional bramble Rubus fruticosus habitat, woodland area, and landscape connectivity were important for population stability. Diversity in the structure of woodlands in Europe has decreased over the last 100 years, and the habitats we found to be associated with more favourable dormouse status have also been in decline. The conservation status of the hazel dormouse, and that of woodland birds and butterflies, may benefit from reinstatement or increased frequency of management practices, such as coppicing and glade management, that maintain successional and diverse habitats within woodland.